Análise do processo executivo de alvenaria estrutural: estudo de caso - Guimarães, Victor de Sousa (2018)
The construction method of masonry structural has a practical methodology based by geometrics controls in different phase of execution, with the goal of provide quality and integrity in building. Thus, the work goal was identify what were the executive’s procedures present in building, the frequency that was executed and if was according with the standard. So, the investigation happened in a masonry structural building, located in Cascavel – PR, during three months, where occurred the study of executive’s procedures realized, with the intention of get execution frequency through of list of service checks and investigate the wrong mortar joints and plumbs. The analyze happened through statistical method, that evaluate the execution of employees. The results showed that the performance of employees responsible for the use of concrete blocks was predominantly satisfactory, but although some activities showed a good frequency there were cases of activity with critical frequency, showing some errors in mortar joint and in plumbs out of tolerances of NBR 15961-2 (2011). In contrast, the performance of employee responsible for the grout was poor, because execution frequency was critical in most of its activities recorded. That way, concludes that had variation in the employees performance according with service type realized e that there is necessity of improve for all employees evaluated, to prevent future problems in building.